Silane-based injection methods for moisture protection in ceramic bricks - Szemiot-Jankowska, Natalia; Hoła, Anna (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
Proper understanding of the mechanisms that lead to excessive moisture, as well as the development of effective methods for cutting off the flow of moisture to walls, is crucial for maintaining the durability and aesthetics of brick buildings, including historical ones. This issue is important in the context of protecting material cultural heritage and is consistent with the goals of sustainable development. The article presents the results of preliminary tests of the effectiveness of the protection against moisture of ceramic bricks, which was made using an injection method and a silane-based injection cream. Two injection methods were used: pressure and gravity, and the injections were performed in bricks with three levels of moisture: a permissible moisture content (3%), a moderate moisture content (7%), and a high moisture content (11%). The mass moisture content was determined using the gravimetric method, the spread of the injection agent in the brick was examined using the drop method and scanning electron microscopy, and the chemical composition of the bricks and injection cream was analyzed using X-ray fluorescence. The results of the tests showed that in the case of the analyzed samples, the most effective method was gravity injection applied at the permissible moisture content, while the least effective was gravity injection applied at a high moisture content of the bricks. The biggest difference in effectiveness between the injection methods was observed in high moisture content samples, where pressure injection proved to be significantly more effective. Confirmation of the results obtained requires further research.